2023
DOI: 10.3847/2041-8213/acd7f2
|View full text |Cite
|
Sign up to set email alerts
|

New Observations of Solar Wind 1/f Turbulence Spectrum from Parker Solar Probe

Abstract: The trace magnetic power spectrum in the solar wind is known to be characterized by a double power law at scales much larger than the proton gyro-radius, with flatter spectral exponents close to −1 found at the lower frequencies below an inertial range with indices closer to [−1.5, −1.67]. The origin of the 1/f range is still under debate. In this study, we selected 109 magnetically incompressible solar wind intervals (δ∣ B ∣/∣ B ∣ ≪… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…At such a scale, the corresponding can be estimated using the Alfvén velocity at the outer scale and the observed magnetic power spectrum; a value of seems reasonable (Huang et al. 2023). Assuming a fast reconnection rate of , can easily extend beyond .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At such a scale, the corresponding can be estimated using the Alfvén velocity at the outer scale and the observed magnetic power spectrum; a value of seems reasonable (Huang et al. 2023). Assuming a fast reconnection rate of , can easily extend beyond .…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There is a range of potential values of that one may consider; a reasonable lower bound appears to be the scale at which the turbulent inertial range starts: around at distances of this order (Coles & Harmon 1988; Huang et al. 2023; Lotz et al. 2023).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…approach to generating synthetic turbulence also remains highly relevant. The many recent studies of turbulence as observed by, e.g., Parker Solar Probe (see, e.g., Adhikari et al 2020;Telloni 2021;Parashar & Matthaeus 2022;Huang et al 2023;Lotz et al 2023) provide valuable inputs whereby the transport coefficients of solar energetic particles, for example, may be investigated in the very inner heliosphere. Lastly, it has been shown that cosmic-ray transport coefficients in different astrospheres can potentially play a significant role in the habitability of exoplanets (see, e.g., Herbst et al 2020;Engelbrecht et al 2024).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if magnetic reconnection induces solar wind through jetlets [28], triggered by SFO, then the solar wind [29] may also exhibit pink noise. Indeed, 1/f fluctuation in the solar wind has been observed over many years [30][31][32]. SFO has been detected in the solar corona [33], suggesting the potential observation of 1/f fluctuation in that context as well.…”
Section: Robustness and Inherited 1/f Fluctuationmentioning
confidence: 93%